2021
DOI: 10.3389/fendo.2021.744857
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Hybrid CB1R and iNOS Antagonist MRI-1867 Displays Anti-Fibrotic Efficacy in Bleomycin-Induced Skin Fibrosis

Abstract: Scleroderma, or systemic sclerosis, is a multi-organ connective tissue disease resulting in fibrosis of the skin, heart, and lungs with no effective treatment. Endocannabinoids acting via cannabinoid-1 receptors (CB1R) and increased activity of inducible NO synthase (iNOS) promote tissue fibrosis including skin fibrosis, and joint targeting of these pathways may improve therapeutic efficacy. Recently, we showed that in mouse models of liver, lung and kidney fibrosis, treatment with a peripherally restricted hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The role of the elements of the endocannabinoid system becomes even clearer when one considers how dynamically endocannabinoids and cannabinoid receptors are regulated in the context of skin diseases. A recent study revealed that AEA and 2-AG were elevated 2- to 4-fold in fibrotic mouse skin compared to control skin [ 169 ]. Induction of 2-AG has also been demonstrated to be detectable following 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced ear inflammation of mice [ 170 ] and in a mouse model of contact dermatitis [ 171 ].…”
Section: The Endocannabinoid System In the Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the elements of the endocannabinoid system becomes even clearer when one considers how dynamically endocannabinoids and cannabinoid receptors are regulated in the context of skin diseases. A recent study revealed that AEA and 2-AG were elevated 2- to 4-fold in fibrotic mouse skin compared to control skin [ 169 ]. Induction of 2-AG has also been demonstrated to be detectable following 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced ear inflammation of mice [ 170 ] and in a mouse model of contact dermatitis [ 171 ].…”
Section: The Endocannabinoid System In the Skinmentioning
confidence: 99%
“…In another study, also using the bleomycin-induced fibrosis model, similar results were obtained with CB 1 receptor knockout mice that did not develop fibrosis, whereas activation of CB 1 with ACEA increased leukocyte infiltration and enhanced the fibrotic response to bleomycin [ 358 ]. In a recent report, the peripherally restricted CB 1 /inducible nitric oxide synthase (iNOS) hybrid inhibitor zevaquenabant (MRI-1867) was found to reduce bleomycin-induced fibrosis in mice deficient in the multi-drug resistance gene 1 (MDR1), which encodes the drug efflux transporter p-glycoprotein (P-gp), but not in mice with intact MDR1 expression [ 169 ]. Consistent with the beneficial role of the CB 2 receptor, another recent investigation reported that a dermal formulation of the CB 2 receptor agonist GP1a reduced fibrosis in a mouse model of excitional wound healing [ 109 ].…”
Section: Selected Skin Diseases—pharmacotherapy and Effect Of Cannabi...mentioning
confidence: 99%
“…In some cases, some third-generation compounds have been designed to inhibit more than one molecular target. For example, hybrid inhibitors of the CB 1 receptor and inducible nitric oxide synthase (iNOS) show benefits in alcohol-drinking behaviors [100], kidney diseases [101], liver fibrosis [102], and skin fibrosis [103].…”
Section: Peripherally Restricted Cb 1 Antagonistsmentioning
confidence: 99%
“…JD5037 is a peripherally restricted CB 1 inverse agonist developed by Jenrin Discovery and licensed to Corbus Pharmaceuticals (now CRB-4001), which is due to begin phase 1 testing in the first half of 2022 (https://www.corbuspharma.com/our-pipeline/ endocannabinoid-system (accessed on 10 September 2021)). [85,105] Prader-Willi syndrome [88] Chronic kidney disease [101] Diabetic nephropathy [93] Alcoholic liver steatosis [94] Alcoholism [99,100] Non-alcoholic liver steatosis [96] Obesity-related liver steatosis [95] Liver fibrosis [102] Pulmonary fibrogenesis [97,98] Skin fibrosis [103] Inflammatory pain [106,107] Neuropathic pain [107,108] Bone cancer pain [109] Chemotherapy-induced pain [110] Migraine and medication overuse headache [111] Spasticity in multiple sclerosis [112] Gastrointestinal motility in colitis [42,43] Anticipatory nausea [113] Cardiac disease [114] Neuropathic pain [115] Chemotherapy-induced neuropathy [116] Inflammatory pain [115,117,118] Diabetic neuropathy [119] Visceral pain [115] Migraine [120,121] Anticipatory nausea [113] Cystitis [122] Bladder overactivity [123] Gastric lesions [118] Clinical research INV-101 in Prader-Willi syndrome (PWS) and non-alcoholic steatohepatitis (NCT04531150) (Inversago Pharma) TM38837 in healthy subjects [104] (7TM Pharma) GFB-024 in diabetic nephropathy (Goldfinch Bio, NCT04880291) AZ...…”
Section: Peripherally Restricted Cb 1 Antagonistsmentioning
confidence: 99%
“…We have previously reported on the structure–activity relationships (SARs) on peripherally restricted diarylpyrazoline-based dual-target CB 1 R/inducible nitric oxide synthase enzyme (iNOS) inhibitors. The lead-candidate MRI-1867 has shown superior efficacy in the animal models of metabolic and fibrotic disorders and is under clinical development. ,, In an extension of our work on designing CB 1 R antagonists without neuropsychiatric liabilities and reduced lipophilicity, we have characterized a new series of peripherally restricted antagonists of CB 1 R. A significant alteration is the replacement of the arylsulfonyl group in our original series by a substituted alkylaminosulfonyl moiety. This approach has now led us to several compounds which have sub-nanomolar affinity and selectivity for CB 1 R and act as functional antagonists at this receptor.…”
Section: Introductionmentioning
confidence: 99%